Aspirasi Partai Demokrasi Indonesia Perjuangan Dalam Pemberdayaan Perempuan - Handayani, Triana Dianita; Geraldy, Galang; Ainul Yakin, Moch; Launda , Launda; purwati, enik (PENITI BANGSA (Pemanfaatan Ilmu Pengetahuan dan Teknologi bagi Masyarakat), 2024)
The battle of the political parties' legislative candidates ahead of the 2024 presidential and vice-presidential elections is heating up. Legislative candidates are diligently campaigning to get the most votes in anticipation of the general elections to be held on February 14, 2024, with the goal of including women in the list of permanent legislative candidates of 37.7%. The end of the general election with the fulfillment of the quota of women from various proposing parties. In Javanese philosophy, women are identified with 3M (Three M) namely Macak (adorning), Manak (giving birth) and Mapan (serving husband) or heaven and hell following husband. The form of women's powerlessness in their nature, which is always regulated in everyday life. How can women be empowered, they must have skills to achieve the same / equal position and be respected. The concern of the PDI-P, seeing the failure of women in their constituency to cultivate catfish in buckets, gave rise to the initiative of the PDI-P legislative candidate Indah Kurnia to provide assistance as a form of her party's aspiration. The goal is to continue to empower women to have income/skills/insight by cultivating catfish in buckets using hydroponic technology. It is hoped that this aspiration will inspire women who are powerless to become empowered women.